Exposure to violence and self-reported aggression among a sample of high school learners in the Stellenbosch district - Sullivan, Daniel Lawrence (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScPsy)--University of Stellenbosch, 2005.